Numerical analysis and optimization of the microwave plasma source for ion beam neutralization - Medhisuwakul M. (2014)
A microwave plasma source operated at a frequency of 2.45 GHz has been used for ion beam neutralization. It could provide a sufficient number of electrons to neutralize a high current ion beam. However, it was operated with high reflection powers. Experimentally changing waveguide dimensions to get an optimum operating condition is difficult, time-consuming and cumbersome. The key approach for a good and stable working plasma source is to get the right dimensions, by three-dimensional simulation tools. Therefore, a three-dimensional computer simulation program was used to calculate the microwave parameters, and to reveal the behaviour inside the source. It utilizes a single block, non-self-consistent model with Drude dispersion to represent the plasma. For this model the plasma angular frequency, ωp, and the electron-heavy particle collision frequency, νe, have to be investigated. This simple yet powerful model allows the analysis and optimization of the source to identify the best dimensions. © 2006 IOP Publishing Ltd.